Russia’s Tatars in the stationary trade of Petropavlovsk in the second half of the 18th – early 20th centuries - Elza M. Gibadullina (Историческая этнология, 2020)
The article analyzes the role of Tatars mobilized by the Russian Empire’s government in the process of economic development of the Kazakh steppe and spreading the experience of organizing stationary forms of trade there. The author points out the importance of socio-cultural closeness between identities of Kazakhs and Tatars, that allowed the latter to succeed in outbound periodic trade in auls. Such type of distribution became a mandatory element of stationary trade due to the nomadic type of the local population’s economy. The article highlights the ability of Tatars to select high-demand goods for sale, create and maintain trade relations. The author draws a conclusion that Tatars became active participants in the process of forming a stationary trade network and the city infrastructure of Petropavlovsk.